ANALYSIS OF COMMUNITY DEVELOPMENT ZAKAT PROGRAM AT INSTITUTIONS NATIONAL ZAKAT AMIL AGENCY JAKARTA - Kartika, Rini Fatma; Idrus, Ali; Gündüzöz, Güldane (JURNAL AL-IJTIMAIYYAH, 2024)
The purpose of this research is to find out how the programs conducted by BAZNAS in the Zakat Community Development Division are used to develop the community. This research focuses on the impact the beneficiary community receives through Zakat Community Development (ZCD). Zakat is an act of worship that all Muslims must do. This research was conducted at the Office of the National Amil Zakat Agency (BAZNAS), which is the only official body established by the government based on Presidential Decree No. 8 of 2001, has the task and function of collecting and distributing Zakat, Infaq, and Sadaqah (ZIS) at the national level. This research is qualitative. The primary data source is the Head of BAZNAS. Data collection techniques include interviews, observation, and documentation. Data analysis techniques with data collection, presentation, reduction, and conclusions. Based on the analysis results through interviews and observations made during the research, it can be concluded that the management of the environmental development program has been running by the program's objectives, namely reducing the poverty rate by an average of 3% each year.